Spheroidization and Its Effect on the Decrease in Mechanical Strength of Steel SA210 Gr. A1 - Titis Aditya; Winarto (Green Publisher Indonesia, 2026)
SA210 Gr. A1 is an important material used in piping systems and boiler components due to its high mechanical strength and resistance to high temperatures. However, long-term exposure to high temperatures can cause microstructural degradation through the spheroidization process, which results in a decrease in mechanical properties. This study aims to evaluate the effect of the spheroidization process on the mechanical strength and microstructure of SA210 steel Gr. A1. The methods used include spheroidization heat treatment at 660°C with time variations of 3, 10, and 100 hours, followed by Vickers hardness testing and tensile testing per ISO 6892-1. After 100 hours of spheroidization, ultimate tensile strength (UTS) decreased from 51.5 to 43.9 kgf/mm² (15% reduction), yield strength (YS) decreased from 44.7 to 28.4 kgf/mm² (36% reduction), and Vickers hardness decreased from 169 to 141 VHN (17% reduction). Elongation increased from 28% to 47% (68% increase), indicating significantly improved ductility at the cost of strength. Results show that spheroidization contributes to a decrease in tensile strength (UTS) and yield strength (YS), but increases the ductility (elongation) value and decreases the hardness of the material. This transformation makes the material more ductile, but at the cost of reduced mechanical durability.